Perdagangan Bebas dan Peran Negara dalam Perspektif Berbagai Sistem Ekonomi - Norhayati Norhayati; Annisa Ariani; Erwan Setyanor (Jurnal Pajak dan Analisis Ekonomi Syariah, 2026)
Free trade is one of the central issues in the dynamics of the global economy, sparking debates about the extent to which the state should be involved in economic activities. Each economic system holds a different perspective on the relationship between market mechanisms and state intervention. This article aims to analyze the concept of free trade and the role of the state from the perspective of various economic systems, namely liberal, socialist, mixed, and Islamic economic systems. The research method employed is a literature review, examining relevant sources such as books, scholarly journals, and other academic references. The findings indicate that the liberal economic system tends to emphasize market freedom with minimal state involvement, whereas the socialist system positions the state as the main regulator in trade. The mixed economic system seeks to balance the roles of the market and the state, while Islamic economics permits free trade as long as it is conducted in accordance with the principles of ethics, justice, and social responsibility. This article is expected to contribute academically to a better understanding of the differing approaches of economic systems toward free trade and the role of the state in addressing global economic challenges.